Analysis and compensation of voltage unbalance of a DFIG using predictive rotor current control. (February 2016) - Phan, Van-Tung; Logenthiran, Thillainathan; Woo, Wai Lok; Atkinson, Dave; Pickert, Volker
Highlights: Generating proper reference rotor currents to compensate voltage unbalance of DFIG. These reference currents include both positive and negative sequence components. The proposed PCC in the RSC will improve the rotor current control accuracy. Compensating the control delay in the PCC will achieve high control bandwidth. Abstract: This paper analyzes the unbalance problem of a stand-alone doubly-fed induction generator (DFIG) under unbalanced loads and proposes a compensation method to balance the stator output voltage. The proposed compensation method is developed based on a predictive current control (PCC) method implemented in the rotor current controller. The development of the PCC is based on the discrete model of the DFIG to predict an appropriate average rotor voltage vector to eliminate the rotor current error in the following switching period. The identified rotor voltage vector is then applied to the rotor-side converter (RSC) by using space-vector modulation (SVM) with constant switching frequency. To improve the control performance, a compensation method for time delay based on the prediction of the future rotor current at the end of current sampling period also is investigated. The proposed control scheme was tested by experiments with 2.2 kW DFIG to demonstrate its excellent steady-state performance as well as extremely fast dynamic response.